Turkey : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2003)
This paper discusses the first Report on Observance of Standards and Codes (ROSC) for Italy. IMF staff reviewed developments in Italy's observance of fiscal transparency practices, with a view to updating changes in current practices, reviewing progress in implementing the initial ROSC's recommendations, and identifying developments relevant for future observance of good fiscal transparency practices.